(untitled) (Global Journal of Management and Business Research, 2021)
Discursive constructions are laden with meaningstied to the historical and social context, which are linked. Historically, the development of concepts associated with Administration is presented in a de contextualized and anachronistic way, which could indicate a manipulative ideological potential. Therefore, this article analyzes the concept of competition, which is so dear to Administration, in the context of the origin of modern organization: the United States railway companies. Thus, through use of the Infinite Conceptual Puzzle, journalistic articles were selected from the American Railroad Journal, for an analysis of the conceptions of competition between 1870 and 1880.